2020
DOI: 10.1016/j.tranpol.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of high-speed train, air and coach services in the spread of COVID-19 in China

Abstract: To understand the roles of different transport modes in the spread of COVID-19 pandemic across Chinese cities, this paper looks at the factors influencing the number of imported cases from Wuhan and the spread speed and pattern of the pandemic. We find that frequencies of air flights and high-speed train (HST) services out of Wuhan are significantly associated with the number of COVID-19 cases in the destination cities. The presence of an airport or HST station at a city is significantly related to the speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(145 citation statements)
references
References 29 publications
7
130
1
1
Order By: Relevance
“…Sokadjo and Atchadé ( 2020 ) found that at the global level, passenger air traffic is positively related to the number of infections. Zhang et al (2020a) showed that infection cases in China were strongly associated with frequencies of flights and high-speed trains, while Zhang et al (2020b) revealed the imported case risk imposed by foreign countries on Chinese provinces and further confirmed the effectiveness of China's strict restriction on inbound flights after March 26 in dramatically reducing the imported case risk. From a different angle, Zhang et al (2020) and Cartenì et al ( 2021 ) observed a strong positive correlation between transport accessibility and the infection cases in Japan and Italy, respectively.…”
Section: Association Between Transport and The Spread Of Covid-19mentioning
confidence: 78%
“…Sokadjo and Atchadé ( 2020 ) found that at the global level, passenger air traffic is positively related to the number of infections. Zhang et al (2020a) showed that infection cases in China were strongly associated with frequencies of flights and high-speed trains, while Zhang et al (2020b) revealed the imported case risk imposed by foreign countries on Chinese provinces and further confirmed the effectiveness of China's strict restriction on inbound flights after March 26 in dramatically reducing the imported case risk. From a different angle, Zhang et al (2020) and Cartenì et al ( 2021 ) observed a strong positive correlation between transport accessibility and the infection cases in Japan and Italy, respectively.…”
Section: Association Between Transport and The Spread Of Covid-19mentioning
confidence: 78%
“…They may have come into close contact with its carriers (i.e., the population flow out of Wuhan), which may have introduced COVID‐19. Because the majority of the PPW spread to Hubei, Guangdong, and Zhejiang provinces (Jia et al, 2020), and also due to the low probability of contact and reasonable protection measures taken by transportation systems (Y. Zhang, Zhang, et al, 2020), the impact of population migration was relatively lower than the population moving out of Wuhan.…”
Section: Discussionmentioning
confidence: 99%
“…The slow and weak emergency response could not prevent epidemic spread caused by population mobility. According to the correlation characteristics and attribution analysis (Table 2 and Figure 5), the PPW played a positive role in developing the epidemic situation in Heilongjiang due to the advanced transportation system (Y. Zhang, Zhang, et al, 2020). The above is closely related to the following fact: Heilongjiang province showed a rising trend when the epidemic situation was generally stable throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…This is unquestionably due to its high infectiveness, but it would not have reached the planetary scale if not for the interconnectedness of the world we live in. As Zhang et al describe in their paper, the centrality of Wuhan and its multiple transport communication hubs (roadways, railways, airports, and boats) played an important role in the spread of the virus in China in the early days of the infection, showing that those regions that required the least travel time from that city were hit earlier and more fiercely [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the already mentioned work by Zhang et al used a kind of gravity model based on the number of infections, which performed a regression analysis of various means of transport in order to investigate how relevant their contribution to the spread of the virus was [ 1 ]. But this kind of papers will not be analyzed here because, as already stated, the study of the contribution to the spread of the virus brought by different modes of transport is out of the scope of our investigations.…”
Section: Introductionmentioning
confidence: 99%